THERMAL CIRCUIT CALCULATION AND REAL-TIME ANALYSIS OF LED LIGHT_x000D_ SOURCE LUMINAIRES - (:unkn) unknown (My University, 2020)
In semiconductor luminaires, thermal circuit design is important since_x000D_ operating temperature directly affects performance and life of luminaires. In_x000D_ this study; In order to keep operating temperature of LED light source_x000D_ luminaires normal, thermal circuit is emphasized. In this context, necessary_x000D_ information about LED and thermal resistance calculation are given in this_x000D_ study. As a real-time application, 10 different power luminaires have been_x000D_ determined on market, thermal resistance calculations have been made_x000D_ depending on heat that needs to be removed and required area calculations_x000D_ have been made for heatsink that needs to be used. Comparative analysis of_x000D_ thermal circuit area calculation results were made with existing heatsink_x000D_ areas of luminaires. Accordingly, it was concluded that thermal circuit_x000D_ designed luminaires which has insufficient heat sink area have a shorter life_x000D_ of approximately 22.7% compared to others.